2013
DOI: 10.1186/1471-2474-14-23
|View full text |Cite
|
Sign up to set email alerts
|

Intimate partner violence and Musculoskeletal injury: bridging the knowledge gap in Orthopaedic fracture clinics

Abstract: Intimate partner violence (IPV) is a serious health issue. There have been widespread research efforts in the area of IPV over the past several decades, primarily focusing on obstetrics, emergency medicine, and primary care settings. Until recently there has been a paucity of research focusing on IPV in surgery, and thus a resultant knowledge gap. Renewed interest in the underlying risk of IPV among women with musculoskeletal injuries has fueled several important studies to determine the nature and scope of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…In addition to the previously mentioned acute symptoms, bone fractures and musculoskeletal problems, including dislocation, are a serious risk. Unfortunately, many of the medical professionals who treat these acute injuries and conditions either have misperceptions about IPV, not enough education to identify the signs of IPV, or feel uncomfortable confronting patients about IPV because they do not know how to approach the situation (Sprague, Madden, Dosanjh, Godin, Goslings, Schemitsch, & Bhandari, 2013). A thorough analysis of symptoms correlated with IPV will enable healthcare providers to determine how best to screen for and intervene in the event of suspected IPV.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the previously mentioned acute symptoms, bone fractures and musculoskeletal problems, including dislocation, are a serious risk. Unfortunately, many of the medical professionals who treat these acute injuries and conditions either have misperceptions about IPV, not enough education to identify the signs of IPV, or feel uncomfortable confronting patients about IPV because they do not know how to approach the situation (Sprague, Madden, Dosanjh, Godin, Goslings, Schemitsch, & Bhandari, 2013). A thorough analysis of symptoms correlated with IPV will enable healthcare providers to determine how best to screen for and intervene in the event of suspected IPV.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that the categories showing the most individual frequency (chronic and acute conditions) shared strong connections with physiological systems that have been shown to be impaired at a higher rate among IPV victims, including gynecological and pregnancy related issues, as well as gastrointestinal, cardiovascular, and neurological symptoms. 17-19 It is not surprising that ‘chronic’ and ‘acute conditions’ had the most significant frequency of coding, since most ailments that require medical attention are either established diseases or emergency issues. ‘Acute conditions’ shows many strong connections, because most acute conditions would be coded with whatever body system(s) they were related to.…”
Section: Discussionmentioning
confidence: 99%
“…12 Among orthopedic surgeons, a knowledge gap pertaining to IPV has been identified. [13][14][15][16] Many orthopedic surgeons believe IPV is rare among their female patients, estimating a prevalence of less than 1%.…”
Section: Discussionmentioning
confidence: 99%